The Effect Of Brand Trust And Brand Image On Consumer Loyalty In Buying Online Products At Lazada Indonesia - Eprida Triwahyuni Sianipar (Journal Basic Science and Technology, 2020)
The purpose of this study was to determine the effect of brand trust and brand image partially or simultaneously on consumer loyalty in buying online products at Lazada Indonesia. This study uses a quantitative approach by taking 230 female consumers who were selected as research samples through incidental sampling techniques in the city of Medan. The data was collected through a brand trust scale based on Keller's theory (1993), a brand image scale based on Kotler & Keller's theory (2009) and a consumer loyalty scale based on Griffin's theory (2001).The results showed that brand trust partially had a significant positive effect on consumer loyalty in buying online products at Lazada Indonesia (t=5.751; P=0.000; b=0.412); and brand image partially has a significant positive effect on consumer loyalty in buying online products at Lazada Indonesia (t=7,518; P=0,000; b=0,398); and brand trust and brand image simultaneously have a significant positive effect on consumer loyalty in buying online products at Lazada Indonesia (F=166.798; P=0.000; R=0.771; R2=0.592).